Investments in Human Capital and their Impact on National Economic Development - Khoshimov Sabir Murtazaevich; Ganiev Shahiriddin Vohidovich (International Journal of Scientific Trends, 2024)
The article discusses the concept of human capital, the need to invest in human capital and its impact on the development of the national economy, and also discusses conclusions and recommendations based on international experience for the full use of the physical and intellectual capabilities of the human factor in economic development.